Doxorubicin-Induced Cardiotoxicity: From Bioenergetic Failure and Cell Death to Cardiomyopathy - Carvalho, Filipa S. (2013)
Doxorubicin (DOX) is an anticancer anthracycline that presents a dose-dependent and cumulative cardiotoxicity as one of the most serious side effects. Several hypotheses have been advanced to explain DOX cardiac side effects, which culminate in the development of life-threatening cardiomyopathy. One of the most studied mechanisms involves the activation of DOX molecule into a more reactive semiquinone by mitochondrial Complex I, resulting in increased oxidative stress. The present review describes and critically discusses what is known about some of the potential mechanisms of DOX-induced cardiotoxicity including mitochondrial oxidative damage and loss of cardiomyocytes. We also discuss alterations of mitochondrial metabolism and the unique characteristics of DOX delayed toxicity, which can also interfere on how the cardiac muscle handles a “second-hit stress.” We also present pharmaceutical and nonpharmaceutical approaches that may decrease DOX cardiac alterations in animal models and humans and discuss the limitations of each strategy.